Inside Back Cover: Control of Imine Exchange Kinetics with Photoswitches to Modulate Self‐Healing in Polysiloxane Networks by Light Illumination (Angew. Chem. Int. Ed. 44/2016). Issue 44 (25th August 2016) - Kathan, Michael; Kovaříček, Petr; Jurissek, Christoph; Senf, Antti; Dallmann, Andre; Thünemann, Andreas F.; Hecht, Stefan
Abstract : Knitting small amounts of a bifunctional diarylethene crosslinker (magenta yarn) into a commodity polysiloxane (gray yarn) via dynamic imine bonds leads to soft materials with photocontrollable intrinsic properties, most notably the abililty to self‐heal. In their Communication onpage 13882 ff., S. Hecht and co‐workers describe various photoswitches that can be used to modulate formyl‐group reactivity upon light irradiation.